The evolution of the corporate rules - Cornelissen, Carel (Tax, 2024)
The aim and objective of the intended research under the abovementioned title is as follows: Discuss the ambit of the corporate rules and the purpose for their enactment. Provide an overview of the history of the corporate rules, in general, and some of the major year on year amendments, in particular, since their inception. Highlight the significance of some of the major amendments, express a view on shortcomings, if any, and suggest further amendments, where necessary. Discuss the relevant sections in the new Companies Bill and the affect it may have on the application of the corporate rules. Discuss the extent of group taxation in short and consider, on a very high level, the advantages and disadvantages of introducing a group taxation regime in South Africa.